COMMUNITY EMPOWERMENT THROUGH THE UTILIZATION OF PLASTIC WASTE INTO ECOBRICKS AS AN EFFORT TO REDUCE PLASTIC WASTE IN SIKALANG VILLAGE, SAWAHLUNTO, WEST SUMATRA - Linda Marni; Siti Hardianti Harahap; Aines Putri Burma; Annisa Sahra; Muhammad Ikhwan; M. Riski Wahyudi (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
This community service research focuses on empowering the Sikalang Village community in household plastic waste management through ecobrick creation, serving as a concrete solution to reduce waste and preserve the ecosystem. Conducted over 30 days (June 17 - July 17, 2025) using a Participatory Action Research approach, the activities encompassed planning, door-to-door socialization, plastic waste collection and compaction into bottles, and the assembly of ecobricks into the "SIKALANG" village sign, followed by evaluation and monitoring. The findings reveal a significant increase in community awareness and participation, with a drastic reduction in plastic waste accumulation and the creation of valuable products. This success demonstrates that direct community involvement in waste management is more effective, while also providing productive avenues for residents. Therefore, such empowerment initiatives are highly recommended for broader implementation to achieve a clean and prosperous environment through self-managed waste.